1995
DOI: 10.1002/pca.2800060604
|View full text |Cite
|
Sign up to set email alerts
|

Application of off‐line supercritical fluid extraction—gas chromatography for the investigation of chemical constituents in Curcuma zedoaria

Abstract: Analytical supercritical fluid extraction (SFE) was used to investigate the chemical constituents of Curcuma zedoaria, a very useful Chinese herbal medicine. The qualitative and quantitative analysis of extracts was performed by gas chromatography with mass spectrometry. The effects of pressure, temperature and flow rate of the extracting fluid on the extraction efficiency of SFE were investigated quantitatively. It was found that at a fixed density, changing temperature in a given experimental range had no gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Reports on the applications of mass spectrometry in Chinese medicinal analysis have been increasing rapidly in recent years. Different ionization methods for these mass spectrometric analyses have been published, including electron ionization (EI),1–17 field desorption (FD) ionization,18, 19 252 Cf‐plasma desorption,20 fast atom bombardment (FAB),21–25 matrix‐assisted laser desorption/ionization (MALDI),26, 27 thermospray28 and electrospray ionization (ESI) 29–44. Mass spectrometry, coupled with chromatographic separations such as gas chromatography (GC/MS) and liquid chromatography (LC/MS), is used for direct analysis of components existing in traditional Chinese medicines.…”
Section: Applications Of Various Mass Spectrometric Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on the applications of mass spectrometry in Chinese medicinal analysis have been increasing rapidly in recent years. Different ionization methods for these mass spectrometric analyses have been published, including electron ionization (EI),1–17 field desorption (FD) ionization,18, 19 252 Cf‐plasma desorption,20 fast atom bombardment (FAB),21–25 matrix‐assisted laser desorption/ionization (MALDI),26, 27 thermospray28 and electrospray ionization (ESI) 29–44. Mass spectrometry, coupled with chromatographic separations such as gas chromatography (GC/MS) and liquid chromatography (LC/MS), is used for direct analysis of components existing in traditional Chinese medicines.…”
Section: Applications Of Various Mass Spectrometric Techniquesmentioning
confidence: 99%
“…GC/MS has been demonstrated to be a valuable analytical technique for the analysis of non‐polar components and volatile essential oils extracted from Chinese herbal plants 2–17. Chen et al in 1987 described a method using direct vaporization GC/MS to determine approximately 130 volatile constituents in several Chinese medicinal herbs 2.…”
Section: Applications Of Various Mass Spectrometric Techniquesmentioning
confidence: 99%
“…during optimization of SFE conditions for extraction of active ingredients from Curcuma zedoaria, Ma and co-workers [26] found that the density of the CO 2 and the fluid volume passing through the plant matrix are the most important factors affecting extraction efficiency, whereas increasing the temperature has little effect; 2. when using SFE to extract indirubin (the active ingredient in the herbs Strobilanthes cusia, Isatis tinctoria, and Polygonum tinctorium) Li et al [27] found that faster extraction kinetics were achieved by employing factorial design to optimize experimental variables such as temperature, pressure, modifier concentration, static extracting time, and CO 2 dynamic extracting volume; and 3. it is interesting to note from another study by…”
Section: Supercritical-and Subcritical-fluid Extractionmentioning
confidence: 99%
“…In this context, several workers were demonstrated its antifungal [9] , antiulcer [10] , antimutagenic [11] , hepatoprotective [12] and cytotoxic [6] properties. It is welldocumented that its main active principles are terpenoids, especially sesquiterpenoids [5,6,13,14] which also are produced by cultured cells. [15] C. zedoaria is also commonly used in medicine but with high starch content.…”
Section: Introductionmentioning
confidence: 99%
“…(Zingeberaceae), commonly known as 'yellow zedoary' is aromatic, pungent, bitter and useful in flatulent colic and debility of the digestive organs and also used as an ingredient in bitter tincture of zedoary and anti-periodic pills, a paste of rhizome is useful externally for cuts, wounds, itching and in sprains. [1][2][3][4] Rhizomes are employed in Asian and many other countries, including Brazil, for the treatment of several ailments, such as cervical cancer [5,6] , hepatitis, inflammations [7] and dolorous processes. [8] Several studies have confirmed and also extended most of the mentioned popular uses of this plant.…”
Section: Introductionmentioning
confidence: 99%